Prospects of organic electrode materials for practical lithium batteries - Lu, Yong; Chen, Jun (Nature reviews. Chemistry, 2020)
Organic materials have attracted much attention for their utility as lithium-battery electrodes because their tunable structures can be sustainably prepared from abundant precursors in an environmentally friendly manner. Most research into organic electrodes has focused on the material level instead of evaluating performance in practical batteries. This Review addresses this by first providing an overview of the history and redox of organic electrode materials and then evaluating the prospects and remaining challenges of organic electrode materials for practical lithium batteries. Our evaluations are made according to energy density, power density, cycle life, gravimetric density, electronic conductivity and other relevant parameters, such as energy efficiency, cost and resource availability. We posit that research in this field must focus more on the intrinsic electronic conductivity and density of organic electrode materials, after which a comprehensive optimization of full batteries should be performed under practically relevant conditions. We hope to stimulate high-quality applied research that might see the future commercialization of organic electrode materials. Organic materials can serve as sustainable electrodes in lithium batteries. This Review describes the desirable characteristics of organic electrodes and the corresponding batteries and how we should evaluate them in terms of performance, cost and sustainability.